Pandangan Ulama Dayah Terhadap Konsep Kekerabatan Dalam Penyelesaian Kasus Ahli Waris Pengganti di Aceh - Murlisa, Lia; Suwardi, Suwardi (Prodi Hukum Ekonomi Syariah STAIN Teungku Dirundeng Meulaboh, 2024)
This study examines the evolving issues of Islamic inheritance law, particularly in Aceh. One common problem in society is the case of substitute heirs, where a grandfather passes away, leaving a grandchild whose father had died earlier. In reality, the grandchild is often overlooked, as the father’s prior death is seen as severing the grandchild’s right to inherit. However, Article 185 of the Compilation of Islamic Law asserts that a grandchild whose father predeceased the grandfather is entitled to inherit. This research aims to explore how Aceh’s dayah scholars interpret the concept of kinship in inheritance law and their views on substitute heirs, as well as how they address such cases. The research uses field research methods with a qualitative approach, analyzed descriptively. The findings reveal that Aceh’s dayah scholars differ in their approaches to resolving substitute heir cases due to varying interpretations of kinship concepts and the order of inheritance. Some scholars accept the idea of substitute heirs, allowing the grandchild to inherit from the grandfather even if the father had died first, referencing Article 185 and several verses that ensure the welfare of orphans with a share equal to or not exceeding that of the father. Conversely, other scholars reject the concept of substitute heirs, arguing that neither the Qur’an nor hadith provides explicit and detailed evidence on this issue, thus severing the inheritance right when the father dies first.